Determining the prevalence of methicillin resistant Staphylococcus aureus(MRSA) among commercial pig herds in South Africa - Annandale, C.H. (Cornelius Henry) (University of Pretoria, 2017)
Dissertation (MMedVet)--University of Pretoria, 2016.